PENGARUH PENAMBAHAN EKSTRAK BUNGA TELANG TERHADAP KADAR ANTIOKSIDAN DAN NILAI HEDONIK PADA PERMEN JELLY SUSU KAMBING - Jun Liani Andwi M Tilana,; Nur Asmaq, (Journal of Innovation Research and Knowledge, 2025)
This study aimed to determine the effect of butterfly pea flower (Clitoria ternatea L.) extract addition on antioxidant content and hedonic value of goat milk jelly candy. The research used a Completely Randomized Design (CRD) with 5 treatment levels: P0 (0%), P1 (3%), P2 (6%), P3 (9%), and P4 (12%) butterfly pea extract with 4 replications. Parameters tested included antioxidant activity using DPPH method and hedonic test (aroma, color, taste, texture) with 25 panelists. Results showed that butterfly pea extract addition significantly affected (P<0.01) antioxidant activity and all hedonic parameters. The lowest IC₅₀ value (highest antioxidant activity) was obtained in P4 treatment at 64.70 μg/ml. The highest hedonic values for aroma and texture were in P3 (3.43 and 4.58), color in P4 (4.58), and taste in P4 (3.01). The study concluded that butterfly pea extract addition can increase antioxidant activity and consumer acceptance of goat milk jelly candy